IMPLEMENTASI EDUKASI DAN PEMBENTUKAN BANK SAMPAH BERBASIS ANALISIS STAKEHOLDER SEBAGAI UPAYA PEMBERDAYAAN ANAK DI KABUPATEN BEKASI - Olaf Ingmar; Qurrotul Uyun; Tessa Azzahra (LPPM Institut Pendidikan Nusantara Global, 2026)
Community service programmes such as the implementation of waste banks have sustainability issues; therefore, a framework is needed to address these issues. Stakeholder analysis can be an effort to strengthen the institutional structure, and those responsible for sustainability are designed to involve various stakeholders. The implementation method over a period of two months includes environmental education for children, identification of primary, secondary, and tertiary stakeholders, mapping of influence and interests, and collaborative recommendation analysis. The results of this study show that (1) children experienced an increase in their descriptive understanding of waste and waste banks, but did not experience a significant increase in understanding; (2) stakeholder mapping revealed that the roles of schools, parents, local waste banks, local governments, and community sponsors are determining factors for programme sustainability; (3) this implementation proves that the stakeholder analysis approach is effective in designing a sustainable school-based environmental empowerment model that can be replicated in other areas.